Genetic reporter for live tracing fluid flow forces during cell fate segregation in mouse blastocyst development - Zhang, Youdong; Li, Xin; Gao, Shu; Liao, Yuanhui; Luo, Yingjie; Liu, Min; Bian, Yunkun; Xiong, Haiqing; Yue, Yanzhu; He, Aibin (Cell stem cell, 2023)
Mechanical forces are known to be important in mammalian blastocyst formation; however, due to limited tools, specific force inputs and how they relay to first cell fate control of inner cell mass (ICM) and/or trophectoderm (TE) remain elusive. Combining in toto live imaging and various perturbation experiments, we demonstrate and measure fluid flow forces existing in the mouse blastocyst cavity and identify Klf2(Krüppel-like factor 2) as a fluid force reporter with force-responsive enhancers. Long-term live imaging and lineage reconstructions reveal that blastomeres subject to higher fluid flow forces adopt ICM cell fates. These are reinforced by internal ferrofluid-induced flow force assays. We also utilize ex vivo fluid flow force mimicking and pharmacological perturbations to confirm mechanosensing specificity. Together, we report a genetically encoded reporter for continuously monitoring fluid flow forces and cell fate decisions and provide a live imaging framework to infer force information enriched lineage landscape during development. VIDEO ABSTRACT.